Parallel Lives: Human–Cow Entanglements at a Finnish Prison Farm - Kroløkke, Charlotte; Honkatukia, Mervi (Humanimalia, 2023)
This article investigates cow caretaking practices in a Finnish prison and living gene bank. Building upon work in Feminist Science and Technology Studies, Critical Animal Studies, and Critical Heritage Studies, we seek to understand how human and nonhuman animal lives are partially folded together, while also discussing the worlds cultivated in a space of conservation and incarceration. Empirically, the article draws upon multispecies ethnography undertaken during two separate visits to Pelso Prison in central Finland. We conclude that cows emerge as not simply working animals. They are viewed as valuable genetic material vital to the Finnish nation state as well as given names and granted personalities. Meanwhile, in the company of an endangered cattle breed, inmates gain new value as care-workers and conservationists “saving” the breed. In this space of exception, precarious interspecies lives are interwoven.